Tindak Tutur Ekspresif Dalam Media Sosial X Jurnalis Palestina Anas Al-Sharif (Kajian Pragmatik pada Representasi Emosi Konflik Palestina) - Husna, Hanun Alya; Cholsy, Hayatul (STIQ Amuntai, 2025)
The presence of Israeli propaganda has made it difficult for Palestinian journalist Anas Al-Sharif to report what is happening in Palestine. To ensure that Anas's news can reach the global community, Anas uses social media, especially X, to disseminate information more widely. To gain public sympathy and attention, Anas uses expressive language to encourage the global community by sharing his feelings regarding the conflict he experienced in Palestine. Therefore, this study will discuss the types of expressive speech acts in social media tweets by Palestinian journalist Anas Al-Sharif. This qualitative study aims to describe the expressive speech acts used in social media X by Palestinian journalist Anas Al-Sharif. The data collection method used was note-taking and documentation. The analysis stage used the pragmatic matching method. The results of this study found the function of expressive speech acts that show speech functions, namely (1) determination, (2) anger, (3) frustration, (4) gratitude, (5) complaints, (6) misery, and (7) expressions of sadness. The expressive speech acts found in Anas Al-Sharif's tweets demonstrate subjectivity, which in this case is not considered a violation of journalistic ethics, but rather a way out to seek public sympathy amidst limitations in accessing the outside world and the unbalanced bias carried out by Western media against Israel.